PENGARUH MODAL INTELEKUALTERHADAP KINERJA KEUANGAN PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014 – 2016 - Natalia Ariyani, 14.05.52.0255; Puspitasari, Elen (Students' Journal of Accounting and Banking, 2018)
This study aims to examine and analyze influence intellectual capital to the financial perfomance of banks on Indonesia Stock Exchange period 2014-2016. Population in this study is banking company listed on the Indonesia Stock Exchange in 2014-2016. The sampels selections are using purposive sampling with period of research of multiple linear regression analysis. The result of the research shows that Human Capital Efficiency (HCE) has positive, but not significant of Return On Invested Capital (ROIC). Structural Capital Efficiency (SCE) has positive, and significant of Return On Invested Capital (ROIC). Capital Employed Efficiency (CEE) has negative, and significant of Return On Invested Capital (ROIC). Keywords :Return On Invested Capital (ROIC), Human Capital Efficiency (HCE),Structural Capital Efficiency (SCE),Capital Employed Efficiency(CEE).